The ethics of sense-making - Weichold, Martin; Candiotto, Laura (Frontiers in Psychology, 2023)
In this paper, we contribute to the arising field of "enactive ethics", that is, the application of enactive cognitive science to the field of ethics. To this end, we will make a case that an "ethics of sense-making" should exist. With "sense-making", we mean the permanent everyday embodied activity of interpreting the surroundings we are in, as well as our role in them. In other words, we mean the activity of understanding our environments in such a way that certain things, but not others, stand out as practically meaningful and relevant to us. We argue that sense-making is not a neutral process, but that it can be performed in ethically better or worse ways. For example, one might make sense of a potentially provocative comment either as an insult or as an invitation for a respectful discussion. How one makes sense in this case will affect oneself, the others, and their present and future relations. We propose that it is often helpful to hold humans responsible for their ways of sense-making. This opens up the possibility to transform their sense-making and the worlds they inhabit. This also has significance for their good lifeeudaimonic well-being. In contrast to deontological, consequentialist, and virtue ethical theories, oOur ethics of sense-making has a quite different starting pointfocusses on something which traditional ethical theories do not focus on: It does not focus on actions, choices of consequences, or virtuous character traits, but rather on the ubiquitous activities of sense-making, which, when changed, will still lead to great ethical improvements of people's actions, choices, and character traits.